Thermoelectric Generation in a Pcm-Based Energy Accumulator - Reyes-Salinas, A; Henriquez-Vargas, L; Donoso-Garcia, P; Pailahueque-Barahona, N; Angel-Rodriguez, F (Springer Science and Business Media Deutschland GmbH, 2021)
An existing laboratory scale solar energy accumulator based on phase change materials was adapted to study experimental and analytically its thermoelectric capabilities. Electric power generation levels were assessed to energize low powered systems. Variables of the study were the circulating air velocity at two levels and the cooling convection mechanism on the cold face of the thermoelectric modules. Temperature measurements were made for the circulating air, phase change material and thermoelectric module faces, complementing with voltage measurements for the equivalent electrical circuit. Energy balances carried out in all phases procured three expressions to calculate the efficiencies of air heating and conversion to electrical work. During an hour of operation the system provided electric power within the range 1–65 mW, being this sufficient to energize modern wireless sensors. The use of more thermoelectric modules could produce more electric power without a significant impact on the air heating efficiencies due to the low heat extraction of the modules. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.